In vitro Identification of CACNA1H in the 9th Exon of Childhood Absence Epilepsy (CAE) Patients Using BioEdit and ClustalW2 - Asma Irshad; Nadeem Sarwar; Halema Sadia; Muhammad Afzal; Mazhar Abbas; Sumaira Sharif; Saeeda Kalsoom; Amna Saeed (BioScientific Review, 2021)
Childhood absence epilepsy (CAE) is an autosomal dominant disorder and a heterogeneous familial condition in which family members express absence seizures initially and then show multiple phenotypes of myoclonic epilepsy, including partial or absence seizures and generalized tonic conic seizures. Multiple types of genetic mutations are involved in epilespy.This studywas aimed atinvestigating thecoding regions of CACNA1H gene for analyzing the mutations involved in epilepsy. Blood samples of mutually unrelated true representativesof CAE were collected from the psychiatry department of various hospitals inLahore. DNA wasextracted using the standard protocol and the amplification of the CACNA1H region was achievedwith specially designed primers. Later on,the analysis of the results wascarried out viathe sequencing of target fragments.Sequences wereanalyzed using the BioEdit software and then aligned with the help of the ClustalW2 software. A series of 12 unrelated patients with CAE were screened for mutationsin the CACNA1Hgene. No mutation was found in exon 9a. As already reported, mutations in the exonic sequence of CACNA1Hgene were found in 5 out of 14 CAE patients. Thesechanges were observed in a PCR fragment amplified by primer 2 in the region of the 9thexon. Subsequent analysis of these fragments identified transition mutations (2025G>A) in exon 9.To conclude, there is a need to explore the site of the gene along with other gene mutations causing epilepsy in the local population of Punjab,Pakistan. It will help to develop genetic counseling strategies, gene therapies,and prenatal diagnostic procedures for the said population.Keywords: DNA amplification,epilepsy, mutations,prenatal diagnostic, sequencesCopyright (c) The Authors